Biochar chemistry in a weathered tropical soil: Kinetics of phosphorus sorption - Morales, Marina Moura; Comerford, Nicholas Brian; Behling, Maurel; de Abreu, Daniel Carneiro; Guerrini, Iraê Amaral [UNESP] (MDPI, 2021)
The phosphorus (P) chemistry of biochar (BC)-amended soils is poorly understood. This statement is based on the lack of published research attempting a comprehensive characterization of biochar’s influence on P sorption. Therefore, this study addressed the kinetic limitations of these processes. This was accomplished using a fast pyrolysis biochar made from a mix of waste materials applied to a highly weathered Latossolo Vermelho distrofico (Oxisol) from São Paulo, Brazil. Standard method (batch method) was used. The sorption kinetic studies indicated that P sorption in both cases, soil (S) and soil-biochar (SBC), had a relatively fast initial reaction between 0 to 5 min. This may have happened because adding biochar to the soil decreased P sorption capacity compared to the mineral soil alone. Presumably, this is a result of: (i) Inorganic phosphorus desorbed from biochar was resorbed onto the mineral soil; (ii) charcoal particles physically covered P sorption locations on soil; or (iii) the pH increased when BC was added SBC and the soil surface became more negatively charged, thus increasing anion repulsion and decreasing P sorption.
Keywords: Batch method; Fast pyrolysis; Pretention